REMEDIASI MISKONSEPSI PESERTA DIDIK MATERI GAYA MENGGUNAKAN ASSURE BERBANTUAN SIMULASI PHET DI SMK - Dedi, Hendrikus; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aim of this research is to investigate the effectiveness of the ASSURE model using assisted by PhET simulation in remedied students? misconceptions about heat transfer subject of class X in SMK Negeri 2 Pontianak. The form of this research is pre-experimental by one-group pretest-post test design. The sample of this research is 37 students in X Teknik Instalasi Tenaga Listrik (TITL) class which are chosen by random sampling in technic of intact group. Instrument for collecting the data is 10 questions in form of multiple choice with the opened reasioning. The mean percentage of students misconceptions before remediation by 93% and amounted to 64% after remediation. Based on McNemar test, the change of students? conseptions was obtained ?2hitung (6,64) ? ?2tabel (3,841) for dk = 1 and ? = 5%. The change of students conceptions after they were given remediation. The Cohen's d effect size value is 1.43 and categorized as high, then ASSURE model effective in remedied students? misconceptions. Keywords: Remediation, Misconception, ASSURE, PhET Simulation, Force